Research of ASP service compination model based on workflow - WU Xiao-dong; BU Jia-jun; CHEN Chun (Tongxin xuebao)
A method of ASP service integration based on Workflow and data pump technology was proposed,the method applied workflow technology to realize procedure integratation of ASP serveice,and data pump technology to realize the integration of data.The key of ASP service integration was the control flow with the data stream,the control flow used the workflow technology,but the data stream performance data pump.In the ASP combination model realization technology based on workflow it discussed the thought of ASPWF model,with the establishment steps and designed the engine algo-rithm.It analyzed the SLA flow processing case of telecommunication enterprise operation in example,explained how to unifie the superiorities of workflow and the small granularity ASP combination service model,in order to enhance the whole system efficiency.